2019
DOI: 10.21608/ajbs.2019.64003
|View full text |Cite
|
Sign up to set email alerts
|

Control of the glassy clover snails Monacha cartusiana using Zingiber officinale extract as an ecofriendly molluscicide

Abstract: High population densities of Monacha cartusiana were observed to cause perdition of various economic crops at Sharkia Governorate. The present study was carried out control this harmful pest using ethanolic Ginger extract as a natural and environmentally safe molluscicide.Toxicological tests revealed that low concentration (20%) of ethanolic Ginger extract caused 10 % mortalityof cloversnails after one day of exposure and 66.7% mortalityafter28 days. The highest mortality percentage (90 %) was recorded after 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
3
2
0
Order By: Relevance
“…The normal histological structure of E. vermiculata observed in the current study was similar to that described by Abd El-Atti et al (2019; 2020) and Kandil et al (2020). Histopathological alterations in samples showed that gonad follicles had lost their normal architecture with degeneration of some stages of spermatogenesis and oogenesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The normal histological structure of E. vermiculata observed in the current study was similar to that described by Abd El-Atti et al (2019; 2020) and Kandil et al (2020). Histopathological alterations in samples showed that gonad follicles had lost their normal architecture with degeneration of some stages of spermatogenesis and oogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Histological investigations into the digestive gland of two species in the current study confirmed the presence of three main cell types; digestive, calcium, and excretory cells forming the epithelial wall of the digestive tubules. This finding was in harmony with the findings of other authors who observed these kinds of cells in E. vermiculata (Abd El-Atti et al, 2020), H. pomatia (Chabicovsky et al, 2004), H. aspersa (Snyman et al, 2005), H. vestalis (Sharaf et al, 2015) and M. cartusiana (Abd El-Atti et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Chemical molluscicides used for long times in controlling land snails have many disadvantages such as disruption of natural biological control systems, undesirable effects on non-target organisms and development of pests’ resistance to synthetic insecticides ( Ismail et al., 2015 ; Abd El-Atti et al., 2019 ). About 25 million of agricultural workers were poisoned by pesticides in developing countries every year ( Farag, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several local but exotic plant species in Egypt are screened and demonstrated potential molluscicidal activities against different species of snails ( Abd El-Atti et al., 2019 ). Exotic Eucalyptus globulus (Blue gum trees) native to Australia and endogenous Ricinus communis (Castor) are cosmopolitan plants growing wildly on stream banks at Sharkia Governorate and their products can be obtained easily by farmers for controlling extensive populations of T. pisana snails.…”
Section: Introductionmentioning
confidence: 99%